Measuring Discriminatory Social Norms Against Children With Disabilities to Improve Communication-Based Programs - Stevens, Sarah C.; Sood, Suruchi; Mertz, Nicole; Kostizak, Kelli (Frontiers in Communication, 2020)
In the Europe and Central Asia region, there are at least five million children diagnosed with some type of disability. These children are likely to be subjected to stigmatization and marginalization, which can lead to discrimination and reduction in access to services. A pilot study was developed to examine factors affecting the treatment of children with disabilities from a holistic, systematic perspective. Stratified by the social ecological model, 450 respondents participated in a structured interview designed to measure knowledge, attitudes, norms, marginalization, and stigma. The results yielded four conclusions. First, it showed that professionals did not rate differently on the constructs of the conceptual model when compared to nonprofessionals. Second, norms are likely affecting the treatment of children with disabilities. Third, the study shows that there is not enough emphasis on educating and involving community members to improve the treatment and protect the rights of children with disabilities. Finally, the results emphasize the importance of approaching disability from a comprehensive social ecological perspective.